Hepatocellular Carcinoma Cells Induce Regulatory T Cells and Lead to Poor Prognosis via Production of Transforming Growth Factor-β1 - Wang, Yi; Liu, Taotao; Tang, Wenqing; Deng, Bin; Chen, Yanjie; Zhu, Jimin; Shen, Xizhong (Cellular physiology and biochemistry, 2016)
Background/Aims: Regulatory T cells (Tregs) are associated with a poor prognosis in hepatocellular carcinoma (HCC). The purpose of the study was to explore the mechanisms of Tregs accumulation in HCC. Methods: We analyzed the frequency of Tregs in HCC by flow cytometry and immunohistochemistry. We also established a transforming growth factor (TGF)-β1-knockdown cell line by lentivirus-mediated RNA interference. Mouse CD4 + CD25 - T cells were cultured in supernatants from various cell lines. Results: HCC patients had a high frequency of Tregs, and high numbers of Tregs correlated with a poor prognosis. Liver cancer cells induced Treg production by secreting TGF-β1. In vivo experiments indicated that knockdown of TGF-β1 reduced the numbers of Tregs and metastatic nodules in mice. Conclusions: These results indicate that cancer-secreted TGF-β1 may increase Tregs, and TGF-β1 knockdown might impair immunosuppression in the tumor microenvironment by decrease Tregs.